2000
DOI: 10.1044/jslhr.4301.256
|View full text |Cite
|
Sign up to set email alerts
|

Strength, Endurance, and Stability of the Tongue and Hand in Parkinson Disease

Abstract: Weakness and fatigue in the orofacial system often are presumed to contribute to the dysarthria associated with neuromotor disorders, although previous research findings are equivocal. In this study, tongue strength, endurance, and stability during a sustained submaximal effort were assessed in 16 persons with mild to severe Parkinson disease (PD) and a perceptible speech disorder. The same measures were taken from one hand for comparison. Only tongue endurance was found to be significantly lower in these part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
5
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 100 publications
(103 citation statements)
references
References 39 publications
4
88
5
6
Order By: Relevance
“…A retrospective analysis of data from both studies revealed lower than normal tongue strength and endurance but no differences between PD and normal control subjects for handgrip performance [10]. These findings support the expected decrements in maximal performance, but only for the axial structure tested.…”
Section: Introductionsupporting
confidence: 75%
See 4 more Smart Citations
“…A retrospective analysis of data from both studies revealed lower than normal tongue strength and endurance but no differences between PD and normal control subjects for handgrip performance [10]. These findings support the expected decrements in maximal performance, but only for the axial structure tested.…”
Section: Introductionsupporting
confidence: 75%
“…right hand, left hand) within each item (e.g. finger taps) [10]; scores were recalculated according to common practice, based on a total of 108, weighting each subitem equally.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations